THE EFFECT OF INFORMATION TECHNOLOGY ON THE COOPERATIVE INSURANCE INDUSTRY CASE STUDY: SHIEKAN INSURANCE AND REINSURANCE COMPANY – SUDAN (EMPIRICAL STUDY) - Omer Ali Eltahir (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aimed to investigate the effect of information technology on the cooperative insurance industry, Shiekan Insurance and Reinsurance Company – Sudan as a case study. The study has achieved in the hypothesis that there is a strong positive relationship between the application of information technology system and the development of management and performance of Shiekan Insurance Company. The study found that the majority of dealers in the Sudanese insurance market have weak in dealing with technology. The study concluded that there a clear impact of information technology and achieving a competitive advantage of Shiekan Insurance company. The study recommends the need to move to the use of technology in the insurance sector in Sudan, especially in the Shiekan Insurance Company because it will have a clear impact on the speed of completion of transactions and claims and save costs. Key Words: Sudan, Reinsurance, Cooperative Insurance, Information Technology, Shiekan,